Multiplexed analysis of fixed tissue RNA using Ligation in situ Hybridization. Issue 14 (19th June 2017) - Credle, Joel J.; Itoh, Christopher Y.; Yuan, Tiezheng; Sharma, Rajni; Scott, Erick R.; Workman, Rachael E.; Fan, Yunfan; Housseau, Franck; Llosa, Nicolas J.; Bell, W. Robert.; Miller, Heather; Zhang, Sean X.; et al.
Abstract: Clinical tissues are prepared for histological analysis and long-term storage via formalin fixation and paraffin embedding (FFPE). The FFPE process results in fragmentation and chemical modification of RNA, rendering it less suitable for analysis by techniques that rely on reverse transcription (RT) such as RT-qPCR and RNA-Seq. Here we describe a broadly applicable technique called 'Ligation in situ Hybridization' ('LISH'), which is an alternative methodology for the analysis of FFPE RNA. LISH utilizes the T4 RNA Ligase 2 to efficiently join adjacent chimeric RNA–DNA probe pairs hybridized in situ on fixed RNA target sequences. Subsequent treatment with RNase H releases RNA-templated ligation products into solution for downstream analysis. We demonstrate several unique advantages of LISH-based assays using patient-derived FFPE tissue. These include >100-plex capability, compatibility with common histochemical stains and suitability for analysis of decade-old materials and exceedingly small microdissected tissue fragments. High-throughput DNA sequencing modalities, including single molecule sequencing, can be used to analyze ligation products from complex panels of LISH probes ('LISH-seq'), which can be amplified efficiently and with negligible bias. LISH analysis of FFPE RNA is a novel methodology with broad applications that range from multiplexed gene expression analysis to the sensitive detection of infectious organisms.